Meritocracy 2.0: High-Stakes, Standardized Testing as a Racial Project of Neoliberal Multiculturalism. (January 2016) - Au, Wayne
High-stakes, standardized testing is regularly used within in accountability narratives as a tool for achieving racial equality in schools. Using the frameworks of "racial projects" and "neoliberal multiculturalism, " and drawing on historical and empirical research, this article argues that not only does high-stakes, standardized testing serve to further racial inequality in education, it does so under the guise of forms of anti-racism that have been reconstituted as part of a larger neoliberal project for education reform. This mix of neoliberalism, high-stakes testing, and official anti-racisms that are used to deny structural, racialized inequalities are a manifestation of what the author calls, "Meritocracy 2.0."